A single-phase all-solid-state lithium battery based on Li1.5Cr0.5Ti1.5(PO4)3 for high rate capability and low temperature operation. Issue 25 (12th March 2018) - Inoishi, Atsushi; Nishio, Akira; Yoshioka, Yuto; Kitajou, Ayuko; Okada, Shigeto
Abstract : We report a battery made from a single material using Li1.5 Cr0.5 Ti1.5 (PO4 )3 as the anode, cathode and electrolyte. Abstract : We report a battery made from a single material using Li1.5 Cr0.5 Ti1.5 (PO4 )3 as the anode, cathode and electrolyte. A high rate capability at room temperature and very low-temperature operation (233 K) were possible as a result of the superior ionic conductivity and low interfacial resistance obtained from the single-phase cell design.